Akuntabilitas Pengelolaan Keuangan pada Balai Guru Penggerak Provinsi Maluku Utara - Mutia M. Papuke; Irfan Zam-Zam; E. Hartaty Hadady (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The problem phenomenon that the author examines is related to the transition of BP-PAUD dikmas which was transferred to the Mobilizing Teachers Center on the issue of budget management human resources, which is still not effective because the Mobilizing Teachers Center handles all levels of schools, including Kindergarten/PAUD, Elementary, Middle School, High School, Vocational School and SLB, whereas Previously, BP-PAUD Dikmas handled only one level, namely TK/PAUD. This research aims to find out how accountable financial management is at the North Maluku Province Teacher Mobilization Center. The method used in this research is a qualitative approach. Data collection techniques in this research are through observation, interviews and documentation studies. The results of this research show that the North Maluku Province's financial accountability center is effective, efficient and accountable because the budget implementation process is transparent and accountable in accordance with applicable rules and regulations. And the achievements of the program / activity in accordance with the program/activity implementation plan and budget of the North Maluku Provincial Mobilization Teacher Center and the Performance Agreement of the Head of the North Maluku Provincial Mobilization Teacher Center